Creepers - Gray, Keith (London : Definitions, 2004)
Two fourteen-year-old friends pursue the game of Creeping through the backyards of homes in their neighborhood, hoping to prove their courage and ingenuity while trying to avoid getting caught.
"First published in Great Britain by Mammoth"--T.p. verso.
Bulletin (Center for Children's books).
Horn Book.
L.A. Recommended Foreign Language.
Bulletin (Center for Children's books), January 1998.
Horn Book, September 1997.
Keywords: Friendship -- Juvenile fiction; Games -- Juvenile fiction; Friendship -- Fiction; Games -- Fiction; Ghosts -- Fiction; Friendship -- Fiction; Games -- Fiction; Ghost stories; Ghost stories